PENGARUH METODE PERAWATAN MORTAR BERBASIS SUSPENSI Bacillus subtilis TERHADAP KUAT TEKAN MORTAR - Alvin Alfredo Bara; Remigildus Cornelis; Moses Kopong Tokan (LPPM Universitas Abdurrab, 2026)
This study aims to investigate the effect of curing methods based on Bacillus subtilis suspension on the compressive strength of cement mortar. The curing methods included immersion and wrapping using flannel cloth, non-woven geotextile, and plastic wrapping, with bacterial suspension concentrations of 3%, 6%, 9%, and 12%, and curing ages of 7, 14, 28, and 56 days. Compressive strength tests were conducted on control mortar and bacterial-treated mortar in accordance with standard testing procedures. The results indicate that mortars cured using Bacillus subtilis suspension exhibited higher compressive strength than the control mortar at all curing ages. The strength enhancement became more pronounced at 28 and 56 days, reaching a maximum value of 55.07 MPa for immersion curing, compared to 36.48 MPa for the control mortar. Wrapped curing methods also produced higher compressive strength values than the control, reaching 39.18 MPa, indicating effective moisture retention during the curing process. The variation in bacterial concentration showed an optimum trend, suggesting that compressive strength improvement does not increase proportionally with higher bacterial concentrations. Overall, the findings demonstrate that Bacillus subtilis–based curing methods significantly improve mortar compressive strength and have strong potential as an alternative, practical, and sustainable curing approach.